PENGARUH PELATIHAN DAN PENGEMBANGAN SDM TERHADAP KINERJA PEGAWAI - Made Budiyasa; I Dewa Nyoman Usadha; I Ketut Merta (Nusantara Hasana Journal, 2023)
Performance has become an important trend in managing organizational management systems, both for companies and government institutions. This research was conducted to determine the influence of training and human resource development on the performance of employees of the Badung Regency Education Service, both partially and simultaneously. The method used in this research is a quantitative descriptive method with a data collection instrument in the form of a questionnaire with a research sample of 70 respondents. Data analysis from the questionnaire results was carried out statistically using SPSS by conducting multiple linear regression analysis and hypothesis testing which included the t test (partial) and F test (simultaneous). In the multiple linear regression analysis, the results obtained were Y = 4.927 + 0.312X1 + 0.634X2.+e with a constant of 4.927. The Training regression coefficient was 0.312, and the HR Development regression coefficient was 0.634. From the results of the T test on the Training variable, the calculated t value > t table (2.737 > 1.687) shows that the training variable partially has a positive and significant effect on performance. The results of the T test for the HR development variable obtained a calculated t value > t table (5.582 > 1.687) which shows that the HR development variable partially has a positive and significant effect on performance. Based on the results of the F test simultaneously, an Fcount value of 100.184 > Ftable value of 2.860 was obtained so that the training and human resource development variables simultaneously had a positive and significant effect on the performance variable. Meanwhile, an R-Square value of 0.844 was obtained, which shows that the training and development variable has an effect on performance of 84.40%.